Comparison of Tax Payments in The Era of President Jokowi's Leadership in Periods 1 & 2 (Empirical Study on Food and Beverage Sector Industrial Companies Listed on Idx for The 2017 - 2022 Period) - Muhammad Hidayat (West Science Social and Humanities Studies, 2023)
This study aims to determine the level of difference in tax payments during the leadership of President Jokowi during the leadership of 1 and 2 President Jokowi carried out by food and beverage industry sector companies listed on the Indonesia Stock Exchange (IDX). The study sample was taken using purposive sampling. Researchers used 2018 to 2022 as research years. The Paired Sample t-Test parametric test produces a statement that there are significant differences in corporate tax payments during President Jokowi's 1st and 2nd leadership periods which are calculated with the effective tax rate model. The results showed that tax payments made by companies made a significant difference during President Jokowi's administration for 2 periods.